Accession strategy to hand hygiene by healthcare professionals - Danielle Galdino de Paula; Fabiana Fernandes Pinto; Renata Flávia Abreu da Silva; Vanessa Galdino de Paula (Universidade de Santa Cruz do Sul, 2017)
Background and Objective: Healthcare-associated infections are serious health threat to hospitalized patients and contribute to increased mortality and morbidity. Hand hygiene is the simplest individual measure and lower cost in order to prevent the spread of infections in health care services. The study seeks to analyze the publications related to the strategies used to improve adherence of health professionals to hand hygiene in hospital. Contents: Integrative literature review. The descriptors were used in isolation and the associated descriptor AND;OR, by the following inclusion criteria: work full text of Article kind, published in the period 2008-2015, in Portuguese and English and used the electronic databases MEDLINE , LILACS and SCIELO. The analysis determined eleven strategies most used to improve adherence to hand hygiene in hospital. Conclusion: The availability of better resources and the use of a single strategy sometimes was not enough to increase membership, and often necessary to apply various strategies together with health professionals. KEYWORDS: Cross infection. Hand hygiene. Health personnel.